Archaeological analysis of shell middens in the Beagle Channel, Tierra del Fuego Island - Estévez, Jordi (2001)
An archaeological programme beginning in 1993, in the Beagle Channel, aims to describe the long-term record of maritimal faunal exploitation, and relate it to the environmental record. Results from quantitative analysis of remains from a series of shell midden excavations indicate a remarkably stable and resilient marine biota over the last 6500 years. Only in the previuos century have there been changes in fauna, which might correspond to recent global warming.